Singlet oxygen and optical limiting applications of BODIPYs and other molecular dyes - May, Aviwe Khanya (Rhodes University, Faculty of Science, Department of Chemistry)
A series of structurally diverse novel and previously synthesized BODIPY core dyes are synthesized and characterized in this thesis. These BODIPYs were synthesized using 2-methylpyrrole, 2-ethylpyrrole, 2,4-dimethylpyrrole and 3-ethyl-2,4-dimethylpyrrole as the starting pyrroles. The combination of different pyrroles with the same aldehyde results in BODIPY core dyes that are structural analogues. These core dyes were used as precursors to synthesise halogenated BODIPYs and novel styrylBODIPY dyes, which were successfully characterized using FT-IR and 1H NMR spectroscopy. The halogenated BODIPY core dyes and the styrylBODIPY dyes were also characterized using MALDI-TOF mass spectrometry. The introduction of heavy atoms on the BODIPY core leads to a red shift of the main spectral. In the presence of styryl groups, the main spectral band red shifts to the far red end of the visible region. As expected, the halogenated BODIPY core dyes also had moderate singlet oxygen quantum yields. These halogenated core dyes were found to be suitable as photosensitizers as all the dyes reduced bacterial viability to below 50% during photodynamic antimicrobial chemotherapy (PACT) studies against Staphylococcus aureus. The structure-property relationships studied demonstrate that the presence of protons rather than methyls at the 1,7-positions or iodines at the 2,6-positions results in more favorable PACT activity. This is likely to be related to the greater ability of the meso-aryl to rotate into the plane of the dipyrromethene ligand and suggests that there should be a stronger focus on dyes of this type in future studies in this field. During nonlinear optical (NLO) studies, all the styrylBODIPYs exhibited favorable reverse saturable absorption (RSA) responses. In the absence of methyl groups at the 1,7-positions, the meso-aryl ring lies closer to the Ï€-system of the BODIPY core, enhancing donor (D)"“Ï€"“acceptor (A) properties and resulting in slightly enhanced optical limiting (OL) parameters. Additionally, there is no evidence that the introduction of heavy atoms at the 2,6-positions significantly enhances OL properties. In a similar manner, alkyl substituents at these positions also do not significantly enhance OL properties; this was studied for the first time using 15 with ethyl groups at the 2,6-positions. The combination of z-scan data and transient spectroscopy for 16 demonstrated that the main mechanism responsible for the NLO properties of nonhalogenated BODIPY dyes is one-photon absorption from the ground state followed by ESA in the singlet manifold. From the NLO studies of 25, OL parameters of 1,3,5-tristyrylBODIPY dyes were found to be similar in magnitude to properties of distyrylBODIPY dyes, but to have less favorable optical properties for OL applications. The OL properties of scandium phthalocyanines were assessed for the first time, since the Sc(III) ion, unusually for a first row transition metal ion, is known to readily form sandwich complexes. The presence of a Sc(III) ion does not significantly enhance the OL properties of phthalocyanines relative to those of rare earth metal ions that also form complexes of this type. Because BODIPYs and phthalocyanines typically absorb significantly in the visible region, transparent PBC polymer thin films of disilane-bridged compounds with minimal absorption in this region were studied and exhibited an excellent RSA response. These compounds may be useful in the design of OL materials that can protect the human eye. The optimized geometries and spectroscopic properties of selected BODIPYs were studied. As expected, the presence of bromine, iodine, ethyl and styryl groups at different positions of the BODIPY core leads to a narrowing of the HOMO"“LUMO band gap, which results in a red-shift of the main spectral band. Partial atomic charges have also been calculated for some of the styrylBODIPY dyes studied for application in OL, and electrostatic potential energy maps were also visualized to better assess how the dipole moment of BODIPY dyes can be modulated since this can affect the OL properties. For all the BODIPYs studied, the electronegativity of the atoms present influences charge distribution on the BODIPY structure.
Keywords: Dyes and dyeing -- Chemistry; Phthalocyanines; Photochemotherapy; Active oxygen; Nonlinear optics; Time-dependent density functional theory; Photochemistry